(untitled) (Journal of Health, Technology and Science (JHTS), 2024)
The skin of mangosteen fruit (Garcinia mangostana) contains tannin and flavonoid compounds that are antioxidants and able to absorb UV rays. This study aims to determine the effect of lip balm preparation formulation on physical stability using mangosteen peel extract as a lip moisturizer. The method used in this study is a laboratory experimental method which includes the extraction stage of mangosteen fruit peel with 96% ethanol solvent, with a concentration of 10%, 15% extract, 20% extract. Evaluation of lip balm preparations includes examination of stability, organoleptic, homogeneity, pH, adhesion, viscosity and melting point. The results showed that the preparation of lip balm mangosteen peel extract (Garcinia mangostana) has a brown color, a distinctive citrus aroma, and a soft texture that is easy to smear. It has a melting point range of 50-70̊°C and a Ph range between 4.5-6.5. There are no changes in color, aroma, and texture on organoleptic tests during the storage period. Lip balm preparations also have a homogeneous composition. Based on the results of statistical tests, it can be concluded that there is an influence of extract concentration in formulations I, II, and III on the physical stability of the preparation. Based on the results obtained in cycling tests both before and after cycling tests in F1, F2 and F3 have good and stable physical stability in accordance with existing libraries.